Novel benzofuran-based sulphonamides as selective carbonic anhydrases IX and XII inhibitors: synthesis and in vitro biological evaluation. (1st January 2020) - Abdelrahman, Mohamed A.; Eldehna, Wagdy M.; Nocentini, Alessio; Ibrahim, Hany S.; Almahli, Hadia; Abdel-Aziz, Hatem A.; Abou-Seri, Sahar M.; Supuran, Claudiu T.
Abstract: Pursuing on our efforts toward searching for efficient hCA IX and hCA XII inhibitors, herein we report the design and synthesis of new sets of benzofuran-based sulphonamides (4a, b, 5a, b, 9a–c, and 10a–d ), featuring the zinc anchoring benzenesulfonamide moiety linked to a benzofuran tail via a hydrazine or hydrazide linker. All the target benzofurans were examined for their inhibitory activities toward isoforms hCA I, II, IX, and XII. The target tumour-associated hCA IX and XII isoforms were efficiently inhibited with K I s spanning in ranges 10.0–97.5 and 10.1–71.8 nM, respectively. Interestingly, arylsulfonehydrazones 9 displayed the best selectivity toward hCA IX and XII over hCA I (SIs: 39.4–250.3 and 26.0–149.9, respectively), and over hCA II (SIs: 19.6–57.1 and 13.0–34.2, respectively). Furthermore, the target benzofurans were assessed for their anti-proliferative activity, according to US-NCI protocol, toward a panel of sixty cancer cell lines. Only benzofurans 5b and 10b possessed selective and moderate growth inhibitory activity toward certain cancer cell lines.